Rereading Amos 7:8-17 in the context of the "professional" prophets in Nigeria - Uroko, Favour C. (Verbum et ecclesia, 2020)
Examining the prophetic commission in Amos 7:8-17, this article argues that it points towards complete repudiation and disdain for the office of the professional prophets in Israel. This anger of Yahweh against Amaziah, his wife and his children for his role in King Jeroboam’s II bad leadership in Israel were analysed in relation to contemporary professional prophesying in Nigeria. Just like the ancient Israelite society, most Nigerian priests and prophets are interested in prophesying for financial gain from those in leadership positions. This is why most of their prophecies are not geared towards reprimanding political leaders concerning their actions. Instead, the professional prophets conspire against any priest or prophet who tends to speak the truth. It was concluded that for Nigeria to achieve the needed development, priests and prophets should not engage in prophecy for material gain. Intradisciplinary and/or interdisciplinary implications: The research on Amos 7:8-17 in the context of the "professional" prophets in Nigeria is based on the current prophesying for financial gains that are rampant amongst priests and members of the clergy in Nigeria. They never warn political leaders against their wrong actions. It was discovered that most of these prophecies are geared towards gaining inordinate favours, political and financial inducements from those in political leadership. Disciplines implicated include Sociology, Church history and Dogmatics.